The formation of the country's brand in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
"This article is devoted to the problems of the establishment country brand. The authorities suggested the solution of the problems, which are appeared in the process of establishing the country brand. "
Keywords: Brand in the country; The image of Kazakhstan